Determinants of Zoom Fatigue Domain Among Public University Undergraduate Students/ Domain Penentu Kelesuan Zoom Dalam Kalangan Pelajar Prasiswazah Universiti Awam (Sains Humanika, 2023)
Undergraduate students are no exception to using digital devices during the teaching and learning process (TnL) during the COVID-19 pandemic. This situation has given various physiological and mental problems to students due to the transition from traditional teaching and learning approaches to online. The long focus on using digital devices during TnL has brought physical and mental fatigue to students. This research aims to identify the relationship between the five ZOOM fatigue domains (general; visual, social, motivational, emotional) among college students (n=215). A cross-sectional study was conducted using the "ZOOM & Fatigue Fatigue" Scale (ZEF) (Fauville et al., 2021) which contains 15 items used to collect data for general fatigue; visual, social, motivational, and emotional. A Pearson correlation analysis was performed to identify the general fatigue domain relationship; visual, social, motivational, and emotional. The research results found that there is a strong to moderate relationship between the five ZOOM fatigue domains. This finding can help increase awareness of the effects of ZOOM fatigue on students' physical and psychological well-being. Apart from that, this study can help to introduce measures to make adjustments to undergo TnL online among students.
Keywords: Fatigue, ZOOM, general; visual, social, motivational, emotional, teaching and learning (TnL)